AB1343 Impact of a rheumatoid arthritis multi-biomarker disease activity test on clinical practice. (23rd January 2014) - Peabody, J.; Strand, V.; Shimkhada, R.; Chernoff, D.; Lee, R.
Abstract : Background: Assessment of disease activity in patients with RA includes patient and physician reported measures and differs by rheumatologist and practice, resulting in variability in treatment decisions and quality of care. Given multiple and often-expensive therapies with significant potential adverse effects, a more uniform assessment of disease activity may benefit treatment selection and patient care. Objectives: The study estimated the impact of a novel Multi-Biomarker Disease Activity (MBDA) test, Vectra™ DA, on the overall quality of RA patient care and on the assessment of disease activity and treatment decisions. Methods: This was a randomized controlled study. Eighty-one Board-certified rheumatologists were recruited and then randomized into an intervention and a control group. Quality was measured using Clinical Performance and Value (CPV™) vignettes, on-line simulations of clinical cases. CPV™ vignettes have been validated to assess the quality of clinical practice and identify inherent variation in care. To evaluate the impact of the MBDA test, three types of vignettes, representing typical RA cases, were used. Case type A comprised two RA cases that were insufficiently controlled and required the addition of or change in non-biologic DMARDs; Case type B comprised two cases inadequately controlled that required addition of combination or biologic DMARDs; and Case type C comprised two cases adequately treated with DMARDs but with a worsening co-morbidity. The open-ended responses were scored in five domains: taking a history, performing an examination, ordering laboratory and imaging tests, assessing disease activity and prescribing treatment. Scores were the percentage of physician answers that matched explicit evidence-based criteria and expert opinion. Rheumatologists randomly completed two of each of the three case types, one at baseline and one after the intervention, for a total of six vignettes. Before completing the second round of vignettes, the intervention group was given educational materials about the MBDA test. The intervention group also received simulated MBDA test results as part of their second round cases. The outcome measures were the overall quality of care, the quality of disease assessment and treatment and the secondary outcome measures: appropriate use of biologic and/or combination DMARDs, laboratory and imaging tests, and overall resource use. Results: The overall quality scores in the intervention group improved by 3% (p=0.02) post-intervention compared with baseline, versus no change in the control group. The greatest benefit in the intervention group was to the quality of disease activity assessment and treatment, which improved by 12% (p<0.01) compared with no significant change in the control group. The intervention was associated with more appropriate use of biologic and/or combination DMARDs in the co-morbidity case type (p<0.01). Conclusions: In this study, use of the MBDA test in simulated cases improved the overall quality and the assessment of disease activity and subsequent treatment decisions for RA patients. New assessment technologies appear to be an effective means for improving quality of care in RA and should prove useful for rheumatologists in daily practice. Disclosure of Interest: J. Peabody Consultant for: Crescendo Bioscience, V. Strand: None Declared, R. Shimkhada: None Declared, D. Chernoff Employee of: Crescendo Bioscience, R. Lee: None Declared